INCIDENCE OF GROSS GENITAL ABNORMALITIES AND TUBAL IMPATANCIES IN CULLED BUFFALOES (BUBALUS BUBALIS) - VALA, K B; PANCHAL, M T; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
Genital organs of freshly slaughtered buffaloes were examined and out of 131 organs examined, 4 (3.05%) had early pregnancy. 127 non-gravid organs (96.95%) comprised 29 (22.14%) normal and 98 (74.81 %) having gross abnormalities. The affections were found to be the maximum in cervix (51.91 %) followed by uterus (29.01 %), ovary with bursa (20.61 %), fallopian tube (13.74%), vagina (4.58%) and under developed genitalia (3.05%). Among the affections of ovaries and mesovarium, the para-ovarian cysts were found maximum in 13.7 4 per cent specimens followed by ovaro-bursal adhesions (9.16%), luteal cyst (1.53%), follicular cyst (0.76%) and ovarian haematoma (0.76%). Using air insufflations technique, unilateral tubal impatency was found in 8.40 per cent tracts, whereas bilateral impatency in 4.58 per cent genitalia. The rate of tubal blockage at the uterotubal junction, isthmus and ampulla were found to be 69.57, 21.74 and 8.70 per cent, respectively. The uterine disorders comprised of perimetritis (20.60%), endometritis (19.85%), perimetrial cyst (3.05%) and leomyoma (0.76%). The cervical disorders comprised of kinked cervix in 41.98 per cent cases and prolapsed cervical rings in 8.40 per cent buffaloes.